The relationship of age, sex, education, and socio-economic status to newspaper reading patterns. - Lagura, Roce Jane A.
Based on Schramm and White's Psychological Theory of News that personal characteristics affect one's reading preference, the problem was: to find out the relationship of age, sex, education, and economic status to one's newspaper reading patterns., The study used the one-shot survey design. A survey was conducted within a barangay. The respondents were people belonging to different age level, sex, education, and economic status. Out of one hundred (100) respondents, thirty four (34) are eighteen to thirty years old, classified as young; Thirty three (33) are thirty years old and to fifty years old, classified as adult; and thirty three (33) are fifty years old and up, classified as old. (p)Interview schedule with close and open-ended questionnaires were used in this study. A chi-square test was performed to establish relationship among different variables. Results showed that generally, reading for Delayed Reward News comes with the increase in age, education and economic status; and that reading for Immediate Reward News are preferred by those with low education, low economic status, and people with younger age. Men tend to read news with greater intensity than women.